STRESS AND ACADEMIC PERFORMANCE IN MATHEMATICS IN INITIAL EDUCATION STUDENTS OF THE CARLOS MEDRANO VÁSQUEZ DE PISCO HIGHER PEDAGOGICAL INSTITUTE - Fajardo Cárdenas, Katty Abigail (2020)
The existence of a relationship between stressand academic performance was investigated, takingas a population the students of the third cycle of theinitial education degree in the area of mathematics,with a sample of 35 students. The research was ofa quantitative approach, of a theoretical basic type,descriptive level and cross-correlational design.In the method followed was the general scientificmethod, the descriptive method and the statisticalmethod; while in the interpretation it was treated withthe inductive deductive method. The proceduresfollowed, observation, evaluation, and diagnosis; indata collection, the diagnostic technique was appliedwith the SISCO inventory, as well as the exam and itsinstrument, the pedagogical test. The statistic to testthe hypothesis was the Spearman's rho coefficientand the data analysis used SPSS version 24 andExcel for windous. It was concluded that no directrelationship was found between stress and academicperformance in the area of mathematics in studentsof the initial education specialty of the HigherPedagogical Institute "Carlos Medrano Vásquez" inthe district of San Clemente, province of Pisco, 2018(P -value = 0.246) with a correlation of 0.469. So it isstated that academic stress is not a determinant foracademic performance.